Sac over the sac - a rare case of subcutaneous dirofilariasis over the lacrimal sac area - Shankar, Mahesh Kumar; Shet, Satish; Gupta, Piyush; Nadgir, Shobha Druva (Nepalese Journal of Ophthalmology, 2014)
Introduction: Dirofilariasis is a rare parasitic infestation in humans. Case: A 33-year-old female from the coastal area presented with a swelling over the right lacrimal sac area. It was clinically diagnosed as a lacrimal abscess and was incised under local anesthesia. A live coiled worm was found and removed along with the cyst. Observations: The worm looked like a thin white thread measuring 101 mm in length. On microscopic examination, the anterior end was slightly tapered and had a rounded head. The H & E stained section of the worm revealed longitudinal ridges with transverse striations on the cuticle. Based on these findings, the worm was identified as dirofilaria repens. Conclusion: Dirofilariasis should be considered in the differential diagnosis of orbital region swelling and conjunctivitis. Surgical removal of the worm not only establishes the diagnosis but also provides a definitive cure. DOI: http://dx.doi.org/10.3126/nepjoph.v6i2.11712 Nepal J Ophthalmol 2014; 6 (12): 224-226